(untitled) (Castilla. Estudios de Literatura, 2020)
A study of what is comical in El Burgués gentilhombre, elaborated using the theory on Poetry and Classical Rhetoric that was taught at the time, paying special attention to the resources that are part of the group called apò tês léxeõs —today called ‘verbal humor’—, used by the artifex to make the audience laugh with the purpose of correcting, entertaining, with the presumptuous extravagance in the way of being, acting, and even writing in people who, abandoning on purpose their natural and simple manners, assume a different behavior and lifestyle with the sole purpose of pretending to be something they are not.